The Use of Ateji as Figurative Speech in Japanese Song Lyrics - Ardisa, Faustina; Novella, Utari (Universitas Pendidikan Indonesia (Indonesia University of Education), 2021)
This study aims to analyze the types of ateji used in Japanese song lyrics, and to analyze ateji as a form of figurative speech by the semantic-semiotic connection between the words used in ateji’s writing and reading. Analysis is done qualitatively based on Shirose’s theory of ateji classification and Japan’s hiyu hyougen (figurative speech) theory. This research resulted in the finding of 4 ateji types in Japanese song lyrics, which are ateji for foreign words pronunciation, ateji for pronouns, ateji for replacing words, and ateji for words used in specific titles/works. The use of metaphor (in’yu), metonymy (kan’yu), and synecdoche (teiyu) are also found between the uses of ateji, based on the relation of the words in said ateji. The words can be linked through contextual relation, conceptual relation, or semantical relation. The connection of the words can also result in similar uses as other figurative speeches not included in Japanese’s hiyu hyougen, which indicated that ateji can be handled and understood as a general form of figurative speech in written Japanese language.